Mediation As an Alternative for Dispute Resolution in Sharia Insurance in Indonesia - Supriyanto, Bambang Heri (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2025)
Mediation is an alternative dispute resolution process that prioritizes a consensus approach in accordance with its consensual, consensus-based, collaborative nature. Mediation can produce a win-win solution. Mediation in resolving sharia insurance problems certainly uses a process in accordance with Islamic values. The reality of resolving sharia insurance disputes is still conventional, namely the system is not sharia-compliant. National Sharia Arbitration Board (Basyarnas) as a permanent and independent body functions to resolve sharia disputes that arise. The discussion of the problem in this paper includes the implementation of mediation as an alternative dispute resolution characterized by its consensual and collaborative approach, potentially producing mutually beneficial results, the parties often turn to Mediation which prioritizes consensual and collaborative processes to reach a common ground in disputes in sharia insurance, the role of mediators in mediation as an alternative means of dispute resolution in sharia insurance and also the driving and inhibiting factors of the mediation process at the Indonesian Muamalat Arbitration Board (Basyarnas). The conclusion is the implementation of the mediation process in resolving sharia insurance disputes in Indonesia. Primarily as a solution to resolve dispute problems in sharia insurance that occur, mediation is consensual or consensus and collaborative. Mediators in resolving sharia insurance problems quickly, precisely, comprehensively in order to maintain conducive conditions, in order to maintain the investment climate and public interest in sharia insurance. Factors in the mediation process to resolve sharia insurance conflict issues in Indonesia, namely: Limited number of mediators in the insurance sector; Good faith; lawyers; socialization